Assessment of legal instruments in the management of employees’ discipline in the public service commission - Fransis, Lilian Denis (Mzumbe University, 2023)
A dissertation Submitted in the Partial Fulfilment of the requirements for the Award of the degree of Masters of Public Administration (MPA) of Mzumbe University